2013
DOI: 10.11002/kjfp.2013.20.3.330
|View full text |Cite
|
Sign up to set email alerts
|

Food nutritional characteristics of fruit of Cudrania tricuspidata in its various maturation stages

Abstract: This study was conducted to investigate the food value of Cudrania tricuspidata at its various maturation stages. The pH, total acid and reducing sugar contents of its fruit juice were determined to have been 4.2~5.1, 1.4~2.0% and 5.4~8.6%, respectively. The general chemical components of its fruit were observed as 76~80% moisture, 2.2~3.5% crude protein, 1.7~2.9% crude fat, 0.8~1.2% ash and 14.5~16.4% carbohydrate. Its free sugar, glucose and fructose contents were determined. The fructose contents of both it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…In both the puddings with and without acid treatment, hardness, cohesiveness, and chewiness significantly increased in the puddings treated with 0.01% mandarin melon berry only (MA0.0 and aMA0.0) when compared to the control puddings (Con and aCon). A study by Jung Ju Choi You and Noh (2013) has reported that mandarin melon berry had 9.3 mg% of Fe, which is higher than 0.4 mg% of Fe in aronia (Kulling & Rawel, 2008). When added to milk, iron reacts with organic and inorganic phosphates of casein micelles and causes an increase in aggregation (Broyard & Gaucheron, 2015).…”
Section: Resultsmentioning
confidence: 94%
“…In both the puddings with and without acid treatment, hardness, cohesiveness, and chewiness significantly increased in the puddings treated with 0.01% mandarin melon berry only (MA0.0 and aMA0.0) when compared to the control puddings (Con and aCon). A study by Jung Ju Choi You and Noh (2013) has reported that mandarin melon berry had 9.3 mg% of Fe, which is higher than 0.4 mg% of Fe in aronia (Kulling & Rawel, 2008). When added to milk, iron reacts with organic and inorganic phosphates of casein micelles and causes an increase in aggregation (Broyard & Gaucheron, 2015).…”
Section: Resultsmentioning
confidence: 94%
“…C. tricuspidata stem contains a large amount of xanthones (polyphenols) and flavonoids, so it is effective in antioxidant and cytotoxicity (Byun et al, 2019;Shi et al, 2014), and the fruit is effective in antipyretic antibacterial activity, nerve cell protection, and muscle relaxation (Jung et al, 2013;Kim et al, 2018). It has been reported that the C. tricuspidata tree is rich in antioxidants and can be sufficiently obtained by hot water extraction (Cha et al, 1999).…”
mentioning
confidence: 99%
“…The most abundant polyphenolic compounds at all four stages were chlorogenic acid (1402.43 ± 31.19–2583.11 ± 28.45 μg/g dw), eriodictyol glucoside (900.25 ± 35.43–1981.97 ± 55.78 μg/g dw) and rutin (255.16 ± 24.29–817.94 ± 22.18 μg/g dw) while most of the polyphenolic compounds, including these three compounds, significantly decreased as maturation progressed. Gradual decrease in phenolic compound contents depending on the stage of maturation might be associated with accumulation of soluble solid contents such as free sugars [37] and the reduction of primary metabolism in fruit at the fully mature and overmature stages, resulting in lack of substrates necessary for the biosynthesis of phenolic compounds [38].…”
Section: Resultsmentioning
confidence: 99%